The association between the reduction of body weight and new-onset type 2 diabetes remission in middle-aged Japanese men: Population-based Panasonic cohort study 8 - Matsui, Takaaki; Okada, Hiroshi; Hamaguchi, Masahide; Kurogi, Kazushiro; Murata, Hiroaki; Ito, Masato; Fukui, Michiaki (Frontiers in Endocrinology, 2023)
Aim This study aimed to investigate the association between change in body weight (BW) and type 2 diabetes remission in Japanese men with new-onset type 2 diabetes. Methods This study enrolled 1,903 patients with new-onset type 2 diabetes between 2008 and 2013 from a medical health checkup program conducted by the Panasonic Corporation, Osaka, Japan. The baseline was defined as the year of new-onset diabetes. We assessed the type 2 diabetes remission five years after baseline and the association between the change in BW and type 2 diabetes remission using logistic regression analyses. To evaluate the predictive performance of the change in BW, we employed the receiver operating characteristic curves and the area under the receiver operating characteristic (ROC) curve (AUC). Results The BW loss was associated with type 2 diabetes remission in the participants with a BMI ≥25 kg/m2 but not in the participants with a BMI <25 kg/m2. The odds ratios were 1.96 (95% CI: 1.19–3.29) and 3.72 (95% CI: 2.14–6.59) in the participants with a loss of 5–9.9% and loss of ≥10% for five years, respectively, in the participants with a BMI ≥25 kg/m2 (reference; stable group [0.9% gain to 0.9% loss]). The AUC and cut-off values for the rate of change in BW for type 2 diabetes remission were 0.59 and 5.0%. Discussion Body weight loss of ≥5% effectively achieved diabetes remission in Japanese men with a BMI ≥25 kg/m2 and new-onset type 2 diabetes.